EZH2 Dynamically Associates With Non-coding RNAs in Mouse Hearts After Acute Angiotensin II Treatment - Wang, Shun; Guo, Ningning; Li, Shuangling; He, Yuan; Zheng, Di; Li, Lili; Wang, Zhihua (Frontiers in Cardiovascular Medicine, 2021)
Enhancer of zeste 2 (EZH2) governs gene reprogramming during cardiac hypertrophy through epigenetic remodeling, a process regulated by numerous non-coding RNAs (ncRNAs). However, the dynamic interaction between EZH2 and ncRNAs upon hypertrophic stimulation remains elusive. Here we performed an unbiased profiling for EZH2-associated ncRNAs in mouse hearts treated with Angiotensin II (AngII) at different time points (0h, 4h, 24h). The interactions between EZH2 and long ncRNAs (lncRNAs), Chaer, Mirt1, Hotair and H19, were validated by PCR. RIP-seq analysis identified a total of 126 ncRNAs to be significantly associated with EZH2. These ncRNAs covers all five categories including intergenic, antisense, intron-related, promoter-related and both antisense and promoter-related. According to their changing patterns after AngII treatment, these ncRNAs were clustered into four groups, constantly enhanced, transiently enhanced, constantly suppressed and transiently suppressed. Structural prediction showed that EZH2 bound to hairpin motifs in ncRNAs including snoRNAs. Interaction strength prediction and RNA pull-down assay confirmed the direct interaction between EZH2 and Snora33. Interestingly, two antisense lncRNAs of Malat1, Gm20417 and Gm37376, displayed different binding patterns from their host gene after AngII treatment, suggesting a crucial role of this genomic locus in modulating EZH2 behavior. Our findings reveal the profile of EZH2-associated ncRNAs upon hypertrophic stimulation, and imply a dynamic regulation of EZH2 function in cardiac hypertrophy.